Design, Development, and Evaluation of Nano Carrier Based Formulations - Kardani, Sunil (Asian Journal of Pharmaceutics (AJP), 2025)
The design, development, and evaluation of Nano carrier-based formulations represent a pivotal paradigm in modern drug delivery systems. This abstract provides an overview of the advancements, challenges, and potentials in this dynamic field. Nanocarriers, ranging from liposomes and polymeric nanoparticles to metallic and lipid-based systems, offer unparalleled advantages in targeted drug delivery, mitigating off-target effects while augmenting therapeutic efficacy. The strategic engineering of these carriers allows precise control over drug release kinetics, enhancing pharmacokinetics and fostering sustained therapeutic concentrations. However, the development of Nano carrier-based formulations is not without challenges. The intricate synthesis processes, necessitating precise control over particle size, surface properties, and drug loading capacities, demand robust manufacturing protocols. Ensuring biocompatibility, minimizing immunogenicity, and comprehensively assessing long-term safety profiles remain critical concerns for clinical translation and regulatory compliance. Evaluation methodologies, ranging from physicochemical characterization to in vitro and in vivo assessments, play a pivotal role in delineating the efficacy and safety profiles of these formulations. Cutting-edge techniques such as spectroscopic analyses, advanced imaging modalities, and precise microscopic evaluations enable comprehensive understanding and characterization of Nanocarriers. In conclusion, the design, development, and evaluation of Nano carrier-based formulations stand at the forefront of modern pharmaceutical innovation. Despite challenges, their potential to revolutionize drug delivery systems, enabling precise targeting, controlled release, and enhanced therapeutic outcomes, underscores their significance in shaping the future of medicine. Continued research efforts, technological advancements, and regulatory compliance will further propel the clinical translation and commercialization of these promising formulations.